Product Design of Trolley Wheelchair for Disabled People Using Ergonomic Function Deployment Method - N. Nurfajriah; Mohammad Rachman Waluyo; Halim Mahfud; Fajar Rahayu Ikhwannul Mariati; Dwie Achmad Basyar; Renesha Fitri Asila; Dinda Meimana (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Disability is a problem with the body-function or body-structure, activity limitations, such as individual's difficulty in carrying out actions in life situations. One example of physical disability is a foot disability or an injury on foot that prevents people’s ability in doing activities, where disabled people will find it hard to move from one place to another. Not only needing assistive devices, disabled people who use wheelchairs also need special facilities to do their activities. One of the activities is to shop. In Indonesia there are still no facilities that make disabled people with wheelchairs to shop at supermarkets in ease. Therefore, an innovation is indeed needed to make an integrated, automated, and special trolleys so it can facilitate and increase awareness of the importance of special facilities for disabled people in Indonesia. The EFD (Ergonomic Function Deployment) method is used to design the trolley according to the respondent's wishes. EFD is a development of QFD by adding a new relationship between consumer needs and the ergonomic aspects of the product. The product attributes that is used are derived from the ergonomics aspect which is known as ENASE (Effective, Comfortable, Safe, Healthy and Efficient). The prioritized variables of product design are trolleys for disabled people that run automatically, have an additional trolley basket (opening an additional trolley), have a soft back and seat, and have a strong locking system so that it makes it easier for users with a weight of 0.06048. The priority of consumer needs (Customer Needs) from the results of the HOE design are 3,4,7,8,9.10,11,14,5,6,12,13,16,18,19,1,15,2, and 17 and the Priority of Technical Requirements from the results of the HOE design are C, A, B, E and D